(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
Forests Are One Of The Main Components Of The Environment Because Of Their Importance In Influencing The Ocean In General, Especially With Regard To Climate, Humidity And Rainfall, As Well As Being A Source Of Plant Wealth, Grazing Land And Various Consumer Uses Such As Wood And Recreation.Forests Require Special Protection For Their Particular Violations Related To The Pollution And Indiscriminate Exploitation Of Forest Products Such As Grazing And The Establishment Of Industrial Enterprises. The Law 84.12 Of The General Forest Regulation Defines Administrative Means Of Protection Alongside The Penal Framework. Keywords: Forestry, Public Order, Administrative Control, Licensing, Banning, Binding, Bodies.